Psychotherapists' Knowledge of Guideline Recommendations for the Treatment of Depressed Suicidal Patients - Teismann, Tobias; Düwel, Helena; Eidt, Leandra; Brailovskaia, Julia; Cwik, Jan Christopher (Frontiers in Psychiatry, 2022)
Objective: Clinical practice guidelines present expert consensus on the treatment of mental disorders. Yet, studies have shown that knowledge of and adherence to recommendations are moderate. The aim of the present study was to investigate, whether and to what extent psychotherapists are aware of and follow the German guideline recommendations for the treatment of suicidal depressed patients. Methods: 174 participants (licensed psychotherapists, psychotherapists-in-training) were presented with five groups of guideline recommendations (referring to inpatient admission, psychotherapy, acute pharmacotherapy, pharmacologic relapse prevention, follow-up appointments) and were asked to identify the guideline recommendation and indicate whether they provided treatment according to the guideline. Results: Knowledge and adherence to the guidelines recommendations on psychotherapy and inpatient admission were well present. However, knowledge about pharmacological treatment recommendations was low; same as the knowledge on the necessity of immediate follow-up appointments after discharge of patients hospitalized due to suicidality. Discussion: The results highlight the importance of greater dissemination of various facts about the management of suicidal patients